CLONING AND EXPRESSION OF GENETICALLY ENGINEERED SYNTHETIC ANALGESIC PEPTIDE MOLECULES IN YEAST CELLS AND THERAPEUTIC APPLICATION. - Rao, J.Venkateshwara (International Journal of Psychosocial Rehabilitation, 2020)
The healthier and comfortable life style of age old people and as well as handicapped persons are key indicators for success mile stone achievements in health sector. But in spite of latest equipments and gadgets the old age people and other handicapped persons are compromising on dignity of their life and leading a painful worried life with various ailments impacting their social status and conditions especially pain relaed problems like cancer, osteoporosis, spinal injuries artificial transplantation of limbs or organs,. These are all associated with heavy and chronic pain conditions. Severe pain is the most serious phobic condition for any patient who is undergoing surgical treatments. Even though the modern drugs are giving some analgesic effects, but they are showing more side effects and as well as most of the time they are fatal to organ or patients. In order to minimize the gap we would like to find out more suitable and effective natural novel analgesic peptide molecules by employing genetic engineering methods.Synthetic Analgesic peptide genes were prepared by Gene Cloning Methods. Site directed mutagenesis and codon optimization methods were adopted for development of recombinant synthetic genes. Their suitability of expression are verified insilico methods using various computational bioinformatics Tools like Vector 2.0 and Accelrys DS Modeller.The developed synthetic genes were cloned in suitable vectors and Expressed in Yeast Cells. Clones were purified and tested for their effectiveness of analgesic activities on mice models using hot plate assay method and Tail Immersion Methods.Our Synthetic genetically engineered built products were given prominent results when compared with standard analgesic molecules (55-70% effiency) that are available in market.Therefore, the challenge is encountered by these small synthetic recombinant genetically engineered molecules which competed with commercial well known chemical drugs, which have lot of side effects.